Embryonic Stem Cell-Like Population in Dupuytren's Disease Expresses Components of the Renin-Angiotensin System. Issue 7 (July 2017) - On, Nicholas; Koh, Sabrina P.; Brasch, Helen D.; Dunne, Jonathan C.; Armstrong, James R.; Tan, Swee T.; Itinteang, Tinte
Abstract : Background: The renin-angiotensin system (RAS) mediates cardiac and renal fibrosis. Dupuytren's disease (DD) is a proliferative fibromatosis affecting the hands. This study investigated the expression of the RAS in DD. Methods: 3, 3-Diaminobenzidine (DAB) and immunofluorescent immunohistochemical (IHC) staining for (pro)renin receptor (PRR), angiotensin-converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1), and angiotensin II receptor 2 (ATIIR2) was performed on 4-μm thick formalin-fixed paraffin-embedded sections of DD cords and nodules from 6 patients. Western blotting (WB) and NanoString mRNA analysis were performed to confirm RAS protein expression and transcriptional activation, respectively. Results: IHC staining demonstrated the expression of PRR, ACE, ATIIR1, and ATIIR2 on the ERG + and CD34 + endothelium of the micro vessels surrounding the DD cords and nodules. PRR was also expressed on the pericyte layer of these microvessels. WB confirmed protein expression of PRR, ACE, and ATIIR2 but not ATIIR1. NanoString analysis confirmed transcriptional activation of PRR, ACE, ATIIR1, but ATIIR2 was below detectable levels. Conclusions: We demonstrated expression of PRR, ATIIR1, ATIIR2, and ACE on the embryonic stem cell–like cell population on the microvessels surrounding DD nodules and cords by IHC staining, although the expression of ATIIR1 was not confirmed by WB and that of ATIIR2 was below detectable levels on NanoString analysis. These findings suggest the embryonic stem cell–like cell population as a potential therapeutic target for DD, by using RAS modulators. Abstract : Supplemental Digital Content is available in the text.